Unlocking Educational Quality Through Enhanced Teacher Satisfaction Insights: Membuka Kualitas Pendidikan Melalui Peningkatan Wawasan Kepuasan Guru - Irawan, Farid; Hariasih, Misti (Indonesian Journal of Education Methods Development, 2024)
This study examines how brand image, service quality, and promotion strategies impact teacher satisfaction in WIJABA Sidoarjo, a non-profit educational organization. Using a quantitative approach with 179 teacher respondents, the research reveals a significant positive correlation between these factors and teacher satisfaction. The findings underscore the importance for non-profits to prioritize brand image, service excellence, and effective promotions to enhance teacher satisfaction and overall educational quality. These insights offer actionable guidance for improving educational services and cultivating a positive learning atmosphere. Highlight: Positive link: brand, quality, promotion, teacher satisfaction. Non-profits: focus on brand, service for better education. Improve teacher satisfaction, create positive learning environment. Keywoard: Teacher Satisfaction,Brand Image, Service Quality,Promotion Strategies, Non-profit Education